Analisis Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Initial Public Offering (IPO): (Studi pada Perusahaan Berbasis Teknologi pada Tahun IPO 2013-2021) - Gevira Lovia Anjani; Mochammad Radiva Dwi Putra; Rizky Gustia Supriatna; Dimas Maulana Hasbi; Dito Rinaldo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study aims to analyze changes in the financial performance of technology-based companies before and after conducting Initial Public Offering (IPO) in 2013-2021. The samples used in this study include 22 technology-based companies that have conducted IPOs. The variables used in this study are Current Ratio Assets (CR), Total Assets Turn Over (TATO), Debt to Equity Ratio (DER), and Return On Equity (ROE), with hypothesis testing using paired sample T-test. The results of the analysis show that Current Ratio (CR) and Debt to Equity Ratio (DER) one year before and one year after the company conducts an IPO have a significant effect on financial performance, while Total Assets Turn Over (TATO) and Return On Equity (ROE) do not experience significant changes. The results of this study are expected to provide insight into the impact of IPOs on the financial performance of technology companies and become a reference for investors, company management, and researchers interested in IPOs and the technology sector.